TANTANGAN (CHALLENGES) DAN PELUANG (OPPORTUNITIES) KEGIATAN PERTUKARAN PELAJAR PROGRAM MERDEKA BELAJAR- KAMPUS MERDEKA (MBKM) PADA MAHASISWA DI UNIVERSITAS MUSLIM INDONESIA - Nurjannah Abna; Nurmiati Muchlis; Rezky Aulia Yusuf; Awaluddin Syamsu; Ishaq Shamad (An Idea Health Journal, 2022)
Innovation in the education sector in Indonesia is keeping continues and improves. The implementation of the Independent Learning-Independent Campus (MBKM) in 2021 in all universities (public and private) in Indonesia. The Indonesian Muslim University (UMI) as one of the largest private universities in eastern Indonesia also participates in implementing this program, one of programs is the student exchange. In this student exchange program, there are as many as 30 students who take part in conducting online and offline lectures at UMI. To improve the quality of program implementation at UMI, of course, some evaluation is very necessary. Therefore, this study reports describing the quality of the program from the experiences of students who participated in the student exchange program at UMI by using a SWOT (strength, weakness, opportunities, and threat) analysis. Total sampling was used in determining the sample. Inbound (i) students who took part in the student exchange program at the Indonesian Muslim University with a total of 30 students. Based on the results of the SWOT analysis, it can be concluded that this program must continue to be implemented at UMI seeing the interest of students from external universities from Sabang to Morocco very interested and motivated to join this program at UMI, this program provides benefits to the insight of cultural diversity in Indonesia, scientific competence, and student social skills. Meanwhile, to improve the quality and quality of this program, UMI is advised to provide internet (wifi) facilities that are much wider and faster, lecturers who support courses must be more cooperative and proactive in communicating with MBKM students.